Knowledge and use of medicinal plants by the patients of the diabetes club, San Vicente de Paul hospital, Ibarra-Ecuador 2016 (Horizontes de Enfermería, 2018)
In the present study the knowledge and uses of medicinal plants were determined as part of the treatment of the patients of the Diabetic Club of the Hospital San Vicente de Paul, Ibarra, Ecuador. The qualitative cross-sectional cohort study was performed in 54 patients of 64  year olds, direct interviews and anthropometric data collection were performed. The results indicate that 83% of the patients know and use the medicinal plants in their treatment, either by medical recommendation, friends or acquaintances, 84% do so by improving diabetes and the rest by optimizing other health problems.  The five plants mostly used were aloe (40%), stevia (36%), garlic (36%), onion-leek (31%) and cinnamon (31%). 47% of the patients used the leaves of the plants, 27% said to use the whole plant, 20% used the fruit and 9% the stem. 71% consume the plants through infusions and 2% consumes the plant naturally and freshly. Of the fifteen medicinal plants that claim to consume only three are plants of South American origin, these are stevia, chocho and jicama. It is necessary to disseminate more scientific studies that support popular knowledge about our native plants, in this community and in health professionals related to the treatment of diabetes to be incorporated into the combined treatment of this disease.
Keywords: Medicinal plants; Diabetic Club; Ecuador; aloe; stevia